New peripherally substituted lutetium mono and bis phthalocyanines: Synthesis and comparative photophysical and photochemical properties - Kocaaga, Nagihan; Kutlu, Oznur Dulger; Erdogmus, Ali (WORLD SCIENTIFIC PUBL CO PTE LTD, 2019)
In this study, the synthesis and characterization of mono-(phthalocyaninato) lutetium(III) (1-Cl and 1-F) [Lu-III(AcO)(Pc)] (Pc = phthalocyaninato, AcO = acetate) and bis-(phthalocyaninato) lutetium(III) (2-Cl and 2-Br) [(LuPc2)-Pc-III] bearing halogenated (F, Cl and Br) phenoxy-phenoxy groups are described and verified by IR, H-1-NMR, UV-vis and mass spectrometry. Photochemical and photophysical properties of 1-F,1-Cl, 2-Cl and 2-Br in DMSO are also presented. A comparison between photophysical and photochemical parameters of mono and bis derivatives showed that mono phthalocyanines are better photosensitizers than bis phthalocyanines. Photophysical and photochemical properties of phthalocyanines are very useful for photodynamic therapy applications. Singlet oxygen quantum yields (Phi(Delta)) give an indication of the potential of the complexes as photosensitizers in photodynamic therapy applications. The chloro, fluoro, bromo-phenoxy-phenoxy substituted mono-(phthalocyaninato) lutetium(III) complexes (1-Cl and 1-F) gave good singlet oxygen quantum yields (from 0.86 to 0.80) in DMSO. Thus, these complexes show potential as Type II photosensitizers for PDT of cancer.
Keywords: lutetium(III)phthalocyanine; singlet oxygen; photochemistry; photophysics; MOLECULAR MATERIALS; ELECTROCHROMISM; ZINC; FILMS; DIPHTHALOCYANINE; Chemistry